The Experience of Female Chinese Students from the University of Nottingham whilst doing Part-Time Jobs - Zhuang, Tingting (2016)
This dissertation addresses the benefits and issues of part-time work experienced by female Chinese students at the University of Nottingham. Chinese students are by far the largest group of student migrants in the UK, with a remarkable increase of approximately 60 percent since 2009 (Cassidy, 2015). Part-time work is a big aspect of student life for many reasons. Obvious reasons include financial independence, social networking and gaining work experience for future careers. Through fourteen face-to-face interviews, this research examines motivation, working conditions and positive or negative impacts on the students. A very specific issue that is discussed in detail covers two different cases of harassment at work and the cultural differences and legal awareness that play a key role. Recommendations for appropriate reactions based on the research are made. The dissertation also argues that the motivation of the students to take on part-time jobs is in correlation with the quality of the experiences that were made by these students.